Research on Capture the Maximum Wind Energy Base on Fuzzy PID Controller - Xie, Hong Fang; Wang, Xiao Dong; Liu, Ying Ming; Yi, En Yong (Applied Mechanics and Materials, 2013)
This paper studies the control strategy of doubly-fed wind turbine to capture the maximum wind energy.The maximum wind energy capture is a more important part of the wind generation. Due to random fluctuations of the wind speed, to track the maximum power of wind turbine,we need to constantly adjust the speed of the generator, so that the generation run in the optimal tip speed ratio in different wind conditions,in order to achieve maximum power tracking. In this paper, the stator output indirect control the generator speed to achieve maximum wind energy capture,and decoupling control of active power and reactive power can be achieved.the MATLAB / SIMULINK simulation results verify the correctness and feasibility of this method.